Synthesis of Sialic Acid-Containing Oligosaccharides and Sialylmimetics - Ando, Hiromune; Magesh, Sadagopan (Sialobiology: Structure, Biosynthesis and Function. Sialic Acid Glycoconjugates in Health and Disease, 2013)
Chemical construction of α-glycoside of sialic acid (Sia) is a demanding subject due to the structural disadvantages of sialic acid: the carboxylate group at C1, the deoxy moiety adjacent to the anomeric center, and the glycerol branch from C6. Since Meindl and Tuppy reported the first synthesis of the glycoside of Sia in 1965, the development of stereoselective sialylation has been the subject for intensive efforts. The first part of this chapter will overview the classical methods for sialylation which override the disadvantages and introduce the cutting-edge of methods for α-selective sialylation, exemplifying the stereoselective synthesis of sialyl oligosaccharides. The later part will briefly summarize several strategies used for the design of sialylmimetics and their potential for the development of sialo-pharmaceuticals in treating various human disease states.